Design and development of a microcomputer-based productivity diagnostic prototype utilizing embedded rule-based expert system - Ong, Victoria D.
In response to the pressing need to provide productivity expertise to small and medium-sized enterprises (SME), the study presents a prototype system called Productivity Advisor. It serves as an automated diagnostic tool that acts as a decision-support system for managers, owners, and analysts. The study covers the design and development of the microcomputer-based productivity measurement and advising prototype system for manufacturing firms. In general, it attempts to demonstrate the viability of enabling knowledge-based interpretation of database indices using expert systems technology. The software design is comprised of two modules: a productivity measurement module that prompts users of the system to encode financial data into the system. The second is a productivity diagnostic module that allows interpretation of the measured ratios. The design automates the decision-making process using the expertise of selected human experts in the field of productivity measurement and evaluation. The rule-based expert system program is encoded using a Windows-based expert systems development tool, CLIPS 6.0. To allow heuristic programming on the ratios, the expert system is embedded as part of the front-end FoxPro 2.6 database application. The database system passes these ratios to the expert system in exchange for the diagnosis through an interface program written in Visual C++ 4.1 that uses the dynamic data exchange (DDE) concept. The computer prototype was successfully developed on an IBM-compatible Pentium personal computer. Testing was conducted on the prototype by using ISO 9241 software guidelines and was found to conform to the minimum requirements of the set specifications. In summary, the study displayed the viability of embedding an expert system program into a database application.